Framing Analysis of Islamic Marriage Sermon in Perspective of Gender Equality - Utami, Diyah; Imron, Ali; Handini, Refti (KOMUNITAS: International Journal of Indonesian Society and Culture, 2014)
Knowledge of gender in the context of marriage sermon is closely related to the interpretation of religious doctrines concerning the relationship of men and women. This study aims to understand the perspective of gender equality on Islamic marriage sermon through framing analysis. This study used framing analysis to reveals the frame of a text by using framing devices that are directly related to the central idea of the text and reasoning. The devices are associated with the cohesion and coherence of the text that refer to a particular idea of marriage. Islamic sermons such as text still tend to show discriminatory for example, this can be felt in the reproduction of a sentences like this: such as sentence â€œthe ideal family is where the husband and wife make a living for their household, especially by giving love and education to childrenâ€. The word â€œidealâ€ or â€œgoodâ€ is a framing device. And the phrase, â€œif the wife works outside the home, the family will lose orientationâ€. The word â€œdisorientedâ€ indicates that family whose wife works outside of the house is a failed family. In this case, the wife is used as a scapegoat for the failure of a family as a wife who works outside.Pengetahuan tentang gender dalam konteks pernikahan khotbah berkaitan erat dengan penafsiran doktrin agama tentang hubungan pria dan wanita. Penelitian ini bertujuan untuk memahami perspektif kesetaraan gender dalam khotbah perkawinan Islam dalam analisis perspektif framing. Penelitian ini menggunakan analisis yang mengungkapkan bingkai teks dengan menggunakan perangkat framing yang langsung berhubungan dengan gagasan utama dari teks dan penalaran framing. Perangkat yang terkait dengan kohesi dan koherensi teks yang merujuk pada ide tertentu pernikahan khotbah Islam Teks masih cenderung menunjukkan tindakan diskriminatif, seperti kalimat â€œkeluarga yang ideal adalah di mana suami dan istri mencari nafkah untuk keluarga mereka, terutama dengan memberikan cinta dan pendidikan untuk anak-anak. Kata â€œidealâ€ atau â€œbaikâ€ adalah perangkat framing. Dan kalimat, â€œjika istri bekerja di luar rumah, keluarga akan kehilangan orientasiâ€. Kata â€œbingungâ€ menunjukkan bahwa keluarga yang istrinya bekerja di luar rumah adalah keluarga yang gagal. Dalam hal ini, istri digunakan sebagai kambing hitam atas kegagalan keluarga sebagai istri yang bekerja di luar.